2016
DOI: 10.4067/s0718-381x2016000200022
|View full text |Cite
|
Sign up to set email alerts
|

M/F Changes after T-loop Upper Horizontal Bending in Segmented Arch Mechanics

Abstract: βTi T-type loops are a frictionless, efficient alternative for extraction space closure. Changes in the upper horizontal portion of T-type loops to improve their mechanical behavior have been proposed, but differences in their biomechanical characteristics have not been well described. This stu dy analyzed the biomechanical differences among three T-type loops with differential bends in their upper horizontal portion. Ninety loops (0.017"x0.025" βTi) were bent and randomly divided in 3 groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In other words, the higher the loop height, the larger the M/F ratio generated by the loop. This finding was consistent with those of other studies [13,18,[26][27][28]. Ribeiro et al [13] demonstrated that the M/F ratio increased with increases in the loop height of composite nickel-titanium T-loops.…”
Section: Loop Heightsupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, the higher the loop height, the larger the M/F ratio generated by the loop. This finding was consistent with those of other studies [13,18,[26][27][28]. Ribeiro et al [13] demonstrated that the M/F ratio increased with increases in the loop height of composite nickel-titanium T-loops.…”
Section: Loop Heightsupporting
confidence: 91%
“…For minor changes in the loop height, the conversion of conventional T-loops into M-loops would increase the M/F ratio. Muñoz-Rendón [27] reported that the convex upper bend of M-loops produced an increased total loop moment compared with T-loops because the upper convex bending increased the total loop height. Moreover, Burstone and Koenig [18] reported that the height of the loop matters more than the length.…”
Section: Loop Heightmentioning
confidence: 99%